Co-Design of Water-Saving Prototypes in Rural Areas of Colombia: An Analysis of Student Participation With Social Impact Through poCDIO Framework - Ramirez-Cajiao, Maria Catalina; Payan-Duran, Luisa; Arias-Hernandez, Janeth; Espinosa-Diaz, Edier; Duarte, Diana; Torres, Andres (Journal of Engineering Education Transformations, 2025)
According to the CDIO framework, the skills to Conceive, Design, Implement and Operate products, processes, and systems, are the basic principles of engineering. Engineers Without Borders Colombia, an inter-university group that develops engineering projects with vulnerable communities, understood that engineering education could be applied to real contexts generating social impact through community participation, and added two elements to the CDIO framework: an observation stage and a participatory approach (poCDIO). This paper uses the poCDIO framework to analyze a case study in rural areas of Colombia where a collective process of active learning is generated, bringing engineering education beyond the classroom. There, professors, students and rural communities developed technological solutions for water saving. The analysis of poCDIO within this context allowed the identification of strengths and weaknesses in the development of engineering projects with communities, taking participation and co-design as the main axes of engineering education that can contribute to social change.